2002
DOI: 10.1289/ehp.02110s5699
|View full text |Cite
|
Sign up to set email alerts
|

Brain uptake, retention, and efflux of aluminum and manganese.

Abstract: My colleagues and I investigated the sites and mechanisms of aluminum (Al) and manganese (Mn) distribution through the blood-brain barrier (BBB). Microdialysis was used to sample non-protein-bound Al in the extracellular fluid (ECF) of blood (plasma) and brain. Brain ECF Al appearance after intravenous Al citrate injection was too rapid to attribute to diffusion or to transferrin-receptor-mediated endocytosis, suggesting another carrier-mediated process. The brain:blood ECF Al concentration ratio was 0.15 at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 31 publications
0
59
0
1
Order By: Relevance
“…The transport across the Blood Brain Barrier (BBB) is the first step in the regulation of their level in the brain [7]. In this context it is interesting to note that high aluminium (Al) content was found in temporal cortex and hippocampus and that Al has been demonstrated to significantly alter the BBB permeability [8][9][10] with the consequence of accelerating amyloid aggregation [11]. Furthermore its in vitro co-incubation with either Zn 2+ or Cu 2+ ions was shown to promote precipitation, though possibly not amyloid fibrils formation [12].…”
Section: 1metals and Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport across the Blood Brain Barrier (BBB) is the first step in the regulation of their level in the brain [7]. In this context it is interesting to note that high aluminium (Al) content was found in temporal cortex and hippocampus and that Al has been demonstrated to significantly alter the BBB permeability [8][9][10] with the consequence of accelerating amyloid aggregation [11]. Furthermore its in vitro co-incubation with either Zn 2+ or Cu 2+ ions was shown to promote precipitation, though possibly not amyloid fibrils formation [12].…”
Section: 1metals and Brainmentioning
confidence: 99%
“…fitted) against the available XAS data. The four models are assembled by putting together two identical A [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] ) motif blocked in space. Among the many configurations produced in this way a few of them are retained, those that appear to fulfill the required geometrical and structural constraints.…”
Section: Models Constructionmentioning
confidence: 99%
“…Aluminum uptake and transport across the blood-brain barrier has been investigated using 26 Al AMS and microdialysis. 45,46 Calcium, its concentration, spatial localization and dynamics are important in many neuronal processes, such as signaling, long-term potentiation and depression, 47 53 The routinely achievable limit of quantitation in these measurements is 10 amol of 41 Ca. Although this method cannot compete at present with the sensitivity or the spatial and temporal resolution of fluorescence methods, it may be applicable as an absolute reference for the fluorescent dyes and for labeling a specific pool or pulse of calcium during an experiment.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…In our previous study, we observed positive effects of EA on some biochemical parameters in oxidative stress induced rats [10]. It has been stated that deficiency and redundance of the elements is important for the metabolism [1][2][3]. We have determined in our literature review that effects of EA and HES upon trace element and major elements in aluminum induced rat tissues has not been researched before.…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that there has been a relationship between high level of aluminum and increased risk of a number of pathogenic disorders, such as microcytic anemia, neurodegenerative disorders including dialysis encephalopathy, Alzheimer's disease and Parkinson's disease. Aluminum ions have strong affinity to bio-membranes; they are capable of increasing the cellular oxidative milieu by potentiating the pro-oxidant properties of transition metals [1][2][3]. Hesperetin (HES) and Ellagic acid (EA) are polyphenolic compounds found in a wide variety of fruits.…”
Section: Introductionmentioning
confidence: 99%